USE AND UTILIZATION OF VILLAGE INFORMATION SYSTEM TO MAXIMIZE POPULATION AND ADMINISTRATIVE DATABASES IN PLOSOBUDEN VILLAGE LAMONGAN REGENCY - eko; Sugianto; Erly Ekayanti Rosyida; Pipit Sari Puspitorini; AH. Hasan Bashori; Fera Yuliana (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2023)
Weak archiving systems, correspondence related to services to village communities and the lack of village government regarding population and population data, so this service has the goal of developing Plosobuden Village a village website to facilitate archiving and population administration. The method carried out in the service process is carried out in several stages, namely location surveys, maturation of concepts in the internal service team, asking for input and criticism of village web creations to village officials, finalizing village web concepts and contents internally for the service team, training and assistance in village web operations. to village officials and evaluation. The results of the service show that village officials are very enthusiastic about the village web to facilitate archiving in terms of correspondence and population data archiving. The results of the evaluation are the lack of basic population input data so that the use of the village web cannot be maximized.